Performance evaluation and simulation of AODV using network simulator 3 - Sonali Prasad. (2012)
Recent interest in the field of Plug-in Hybrid Electric Vehicles (PHEVs) becoming a wireless technology has led to tremendous revelations. If the vehicles are considered as wireless nodes of a network, there are endless possibilities of controlling traffic congestion, improving driver safety and developing alert systems in case of accidents. Such a network is known as a Vehicular Ad-hoc Network (VANETs) and in many ways very similar to the well know Mobile Ad-hoc Network (MANETs).However, there are differences since VANETs entail many restrictions for the nodes. An interesting area of research is to see how routing protocols functions in both these networks.